P-Synephrine enantiomers: binary phase diagram, crystal structure and kinetic stability of a metastable conglomerate monitored by nonlinear optics. Issue 36 (2nd September 2020) - Ianno, Veronica; Clevers, Simon; Négrier, Philippe; Dupray, Valérie; Coquerel, Gérard; Espeau, Philippe
Abstract : Crystal structure and kinetic stability of a conglomerate versus the racemic compound of p -synephrine. Abstract : The crystal structure of ( S )-(+)- p -synephrine was refined at 296 K from X-ray powder diffraction. The compound crystallizes in the orthorhombic system P 21 21 21 with four molecules per unit cell and Z ′ = 1. The cell parameters are equal to a = 6.5925(12) Å, b = 7.9915(14) Å, and c = 17.035(4) Å. The melting characteristics of the enantiomers were determined at high DSC scan rates. The pure enantiomers melt at T fus = 176.6 ± 0.9 °C with a melting enthalpy equal to 234.2 ± 3.9 J g −1 . Coupling DSC and crystallographic analysis, a stable binary phase diagram between these chiral molecules was established taking into account the racemic compound. Two symmetrical eutectic invariants at: 172.7 ± 0.5 °C for x = 0.05 and x = 0.95 were found pretty close to the melting temperature of the enantiomers. Additionally, the equimolar mechanical mixture of the two enantiomers led to a metastable conglomerate whose melting temperature was estimated to be 149 °C, thanks to the Schröder–van Laar relation. The activation energy of the transition from the metastable conglomerate toward the racemic compound was estimated to be E a = 145 kJ mol −1 by a nonlinear optical method. This new isothermal second harmonic generation application performed at different temperatures is of general applicability for the assessment of the activation energy associated with the irreversible heterogeneous reaction: < R > + < S > → < RS >.